2013
DOI: 10.1177/0165551512469775
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the quality of information on stroke and speech and language difficulty web sites

Abstract: Online healthcare information is used by patients, their carers and families (PCF) experiencing speech and language difficulties (SLD) after a stroke. This information may be of variable quality. Tools have been designed to assess the risk of poor information quality, evaluating both generic and specific concepts, yet none focus on stroke. The readability of information is also an issue when communication disorders are in consideration. The study investigated the quality and readability of information on 51 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 53 publications
(187 reference statements)
0
16
0
Order By: Relevance
“…5,6 While the Internet is an economical way for content creators to reach a large audience, its popularity is a cause for concern because it remains unregulated and can result in propagation of misinformation. [7][8][9] There are numerous sources of misinformation ranging from uninformed authors to commercial interests and false advertising. 10,11 Internet usage among patients with chronic conditions is of particular interest, as these patients are more likely to use the Internet to seek information about their disease and treatment options.…”
mentioning
confidence: 99%
“…5,6 While the Internet is an economical way for content creators to reach a large audience, its popularity is a cause for concern because it remains unregulated and can result in propagation of misinformation. [7][8][9] There are numerous sources of misinformation ranging from uninformed authors to commercial interests and false advertising. 10,11 Internet usage among patients with chronic conditions is of particular interest, as these patients are more likely to use the Internet to seek information about their disease and treatment options.…”
mentioning
confidence: 99%
“…While other studies have looked into this [38,39] it was not the aim of this work. Furthermore, previous studies have demonstrated that the quality of information was variable and did not correlate with its readability [40]. While the accuracy of the information is undeniably important, it is of little value if it is incomprehensible to those patients reading it due to being written at too high a reading level.…”
Section: Discussionmentioning
confidence: 98%
“…6 The health information available online to consumers is not generally subject to quality checks or regulations-For this reason, there is significant potential for this information to mislead and misinform the general public. [7][8][9] Literature is currently sparse regarding the quality of online health information aimed at patients-It is even more sparse regarding video sources such as YouTube. No studies exist, for example, assessing these factors in relation to rhinoplasty, a common cosmetic surgery procedure.…”
Section: Introductionmentioning
confidence: 99%
“…6 The health information available online to consumers is not generally subject to quality checks or regulations—For this reason, there is significant potential for this information to mislead and misinform the general public. 7-9…”
Section: Introductionmentioning
confidence: 99%